Optical Properties of a-SiC:H Thin Films Deposited by Magnetron Sputtering - Christina Veneti; Lykourgos Magafas; Panagiota Papadopoulou (Electronic Materials, 2025)
In the present work a-SiC:H thin films were prepared using magnetron sputtering technique for different substrate temperatures from 100 °C to 290 °C. Their optical properties were studied using the ellipsometry technique. The experimental results show that the optical band gap of the films varies from 2.00 eV to 2.18 eV for the hydrogenated films, whereas the Eg is equal to 1.29 eV when the film does not contain hydrogen atoms and for Ts = 100 °C. The refractive index has been observed to remain stable in the region of 100 °C–220 °C, whereas it drops significantly when the temperature of 290 °C is reached. Additionally, the refractive index exhibits an inverse relationship with Eg as a function of Ts. Notably, these thin films were deposited 12 years ago, and their optical properties have remained stable since then.